Pengembangan Trainer Mikrokontroler Lengan Robot Sebagai Media Pembelajaran Mengoperasikan Sistem Pengendali Elektronik - Muhammad Zakir; Sukardi Sukardi (Jurnal Pendidikan Teknik Elektro, 2020)
This research is in the background of not yet optimal learning media. Microcontroller trainers in subjects operate an electronic control system (MSPE) in class XI TITL of SMK N 1 Padang. This study aims to determine the validity, practicality, and effectiveness of robot arm microcontroller trainers. This type of research is research and development. This development study used the Bord and gall development model. The research subjects were class XI TITL students at SMK Negeri 1 Padang. Respondents used for practicality tests are class XI TITL students at Padang State Vocational School and MSPE subject teachers. The research instruments used were three, namely validation sheet, practicality questionnaire, effectiveness test using an objective test. Based on the results of the study obtained data validity that is validator 1 by 81%, validator 2 by 83%, teacher practical results by 87.3% and student practical results by 88.90%, the results of the effectiveness test were 89.29.7%. The implication of this study is that if there is a change in the percentage of completeness of student learning outcomes, the trainer can be used as a learning medium